2008
DOI: 10.1111/j.1468-2958.2007.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Friends’ Appearance and Behavior on Evaluations of Individuals on Facebook: Are We Known by the Company We Keep?

Abstract: This research explores how cues deposited by social partners onto one's online networking profile affect observers' impressions of the profile owner. An experiment tested the relationships between both (a) what one's associates say about a person on a social network site via ''wall postings,'' where friends leave public messages, and (b) the physical attractiveness of one's associates reflected in the photos that accompany their wall postings on the attractiveness and credibility observers attribute to the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
422
4
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 600 publications
(451 citation statements)
references
References 38 publications
13
422
4
12
Order By: Relevance
“…Walther and colleagues have shown that an individual (on Facebook) is consistently rated as physically and socially attractive when his or her friends are also attractive (Walther, Van Der Heide, Kim, Westerman, & Tong, 2008). Positive and negative comments left on a person's Facebook wall also greatly influence whether they are seen as attractive.…”
Section: Signaling Theory Warranting Theory and Identity Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Walther and colleagues have shown that an individual (on Facebook) is consistently rated as physically and socially attractive when his or her friends are also attractive (Walther, Van Der Heide, Kim, Westerman, & Tong, 2008). Positive and negative comments left on a person's Facebook wall also greatly influence whether they are seen as attractive.…”
Section: Signaling Theory Warranting Theory and Identity Developmentmentioning
confidence: 99%
“…Teenagers must also add or reject friend requests from their peers, navigating the complicated web of friendship practices (Ito et al, 2009). Finally, the interactions and feedback that one's network provides in SNS-through wall posts and comments-show how complex social identity and peer influence processes occur in these online communities (Subrahmanyam, Reich, Waechter, & Espinoza, 2008;Walther et al, 2008Walther et al, , 2009.…”
Section: Signaling Theory Warranting Theory and Identity Developmentmentioning
confidence: 99%
“…Such a high number of users could be explained by the variety of SNS possibilities. Each SNS user can communicate with friends or strangers, maintain relationships, enlarge their circle of friends, share private information, collaborate or just have fun ( [24]; [51]; [62]; [65]; [67]; [72]). Due to this, many people integrated social network sites in their daily routine ( [43], [65], [72]) and spend there between 10 minutes and 3 hours every day ( [28]; [68]; [62]).…”
Section: Social Network Sitesmentioning
confidence: 99%
“…Apart from that, many people use SNS to share private information like photos or videos or try to enlarge their circle of friends. Others just pursue the aim to collaborate or to have fun while playing online games and compete with friends ( [24]; [51]; [62]; [65]; [67]; [72]). Additionally further SNS (such as Xing or LinkedIn) support the application process of job seekers by providing the possibility to upload CVs, connect with their job network or communicate with recruiters and headhunters for job offers [74].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation